APPLICATIONS OF TRIGONOMETRIC FUNCTIONS TO PROBLEM SOLVING (Лучшие интеллектуальные исследования, 2025)
Annotation: The article gives extensive attention to the applications of trigonometric functions to solving geometric problems, in which various types of geometric problems are solved in several ways using the definitions and properties of trigonometric functions, and geometric problems related to proof are applied to trigonometry and proven in several different ways . The examples and problems presented in the article clearly demonstrate the application of trigonometry to solving various problems in practical concrete examples and problems .